ANALYSIS OF THE APPLICATION OF OCCUPATIONAL SAFETY AND HEALTH MANAGEMENT SYSTEM (K3) IN THE CONSTRUCTION PROJECT OF THE OFFICE BUILDING OF THE DPRD BUILDING PHASE 1 OF THE PROVINCE OF SOUTH KALIMANTAN BANJARBARU - Munawwaroh, Siti; Eliatun, Eliatun (CERUCUK, 2026)
Construction is the process of building facilities and infrastructure in civil engineering and architecture. Construction projects have unique characteristics. The main factor is the location of the workplace, which is exposed to all weather conditions and has limited working hours. Thus, the construction services sector is at high risk of experiencing significant accident costs. A healthy and safe work environment is obtained from the implementation of a well-done Work Health and Safety Management System (SMK3). The purpose of the study was to determine the implementation of SMK3 at the South Kalimantan Provincial Parliament Office Building site and the constraints of SMK3 implementation.Data collection involved interviews and questionnaires to respondents related to OHS to obtain primary data, as well as secondary data from references from books, journals and previous research. The data was then analyzed using product moment correlation testing validity and Cronbach's Alpha method testing reliability and calculating the average value (mean). The variables of the study were the Work Health and Safety Management System (X1) and the Obstacles to the Implementation of SMK3 (X2).The results of the analysis of the implementation of the Work Health and Safety Management System (SMK3) carried out at the location of the South Kalimantan Provincial DPRD Office Building in Banjabaru show that the project has implemented various OSH programs while the most significant obstacle in the implementation of work safety and health is related to the tendency of workers who work without using PPE. Keywords: Occupational Health and Safety (OHS), OHS implementation, OHS Implementation Constraints.